New perspectives on picocyanobacteria and understudied cyanobacterial diversity in the Albemarle Pamlico sound system, North Carolina, USA - Joel Sánchez-Gallego; Joel Sánchez-Gallego; Nathaniel P. Curtis; Hans W. Paerl; Ryan W. Paerl (Frontiers in Microbiology)
Cyanobacteria are important primary producers, sources of secondary metabolites, and sentinels of environmental change in aquatic ecosystems – including large estuaries. Here, we newly investigated cyanobacterial diversity within the Albemarle Pamlico Sound System (APES) using (16S rRNA) gene amplicon sequencing analyses. Substantial cyanobacterial diversity including lineages lacking current isolates were recovered (46 genera, 17 potentially cyanotoxic), with oligohaline waters of the Albemarle Sound and its tributaries being notable regional hotspot for diversity. Salinity and temperature were influential drivers of cyanobacterial community composition. Picocyanobacteria (cells <3 µm in diameter) were abundant in amplicon sequence libraries (72% of cyanobacterial sequences) – especially populations within Synechococcus SubClade 5.2. Picocyanobacteria along with picoeukaryotes were large contributors to total phytoplankton biomass comprising ~47% of chlorophyll a. Further, the picocyanobacterial genera Synechococcus, Cyanobium, and Synechocystis (55.4%, 14.8%, and 12.9% of cyanobacterial sequences, respectively) formed a core community spanning from freshwater regions (eastern AST, D949) to polyhaline environments (NRE100 downstream stations to PS5), suggesting resilience to significant salinity fluctuations and associated environmental changes. Amplicon sequence variant (ASV) and environmental data indicate the presence of several putative ecotypes, as well as distinct abundance patterns among closely related populations, highlighting substantial fitness variability among subspecies. Notably, potentially cyanotoxic genera, Synechocystis, Planktothrix, Plectonema, and Dolichospermum were the four more abundant detected in polyhaline APES regions, far beyond conspicuous freshwater sources. These findings reveal previously unrecognized potential sources of cyanotoxics in estuarine food webs and habitats, underscoring the ecological significance of cyanobacterial community dynamics across salinity gradients.